Clinico-Epidemiological and Allergens Profiles of Dogs with Canine Atopic Dermatitis from Haryana, India - Aditya,; Jhambh, Ricky; Singh, Yudhbir; Lal Jangir, Babu; Kumar Gupta, Akhil (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present investigation was conducted to study the clinico-epidemiology and allergens profile of canine atopic dermatitis (CAD) in  dogs in and around Hisar, Haryana (India). A total of 46 dogs with pruritic dermatological conditions presented at Veterinary Clinical  Complex of the College from April to October, 2022 were screened as per the Favrot’s criteria of diagnosis of CAD and ruling out other  dermatological conditions. Allergens profile of CAD in dogs was established using intradermal testing with a panel of allergens. Clinico epidemiological investigation revealed CAD (45.65%) to be the most common pruritic skin diseases diagnosed, followed by bacterial  dermatitis (13.04%) and pyodemodicosis (13.04%) in pruritic dogs. Labrador retriever was the most common breed of dog affected  with CAD, followed by Pitbull with age predisposition between 6 months to 3 years. Axillae, forepaws and hind paws were the most  common body sites affected with lesions of atopic dermatitis. All the affected dogs qualified ≥6 clinical features of Favrot’s criteria of  CAD with affection of front feet and ear pinnae, sparing the dorso-lumbar area and ear margins. Allergens profile of CAD in affected  dogs revealed both indoor (house dust mites, molds, house dust) and outdoor allergens (plant pollens, allergens of cockroach and  mosquitoes) to be the frequent causes of CAD in dogs in study area. Accordingly, the living environment of the dogs can be adjusted  to avoid the allergen exposure in affected dogs.
Keywords: Allergens profile; Canine atopic dermatitis; Clinico-epidemiology; Dogs; Haryana